Rescuer Exertion and Fatigue Using Two-Thumb vs. Two-Finger Method During Simulated Neonatal Cardiopulmonary Resuscitation - Reynolds, Claire; Cox, Jennifer; Livingstone, Vicki; Dempsey, Eugene Michael (Frontiers in Pediatrics, 2020)
Background: Rescuer fatigue during neonatal CPR can affect CPR quality leading to reduced cerebral and myocardial perfusion. Aim: To investigate rescuer fatigue during simulated neonatal CPR using both objective (heart rate and cardiac output) and subjective measures. Methods: A randomized crossover manikin study performed. 19 doctors working in neonatology were randomized to a) Two-thumb term b) Two-finger term c) Two-thumb preterm or d) Two-finger preterm group. Cardiac output and heart rate were measured with a non-invasive cardiac output monitor. A Likert scale assessed participants’ level of perceived exertion. Results: In the preterm group, the mean change in HR from rest to 5 minutes in the TT group was 11.58 bpm (SD 6.22) vs 9.94 bpm (SD 8.48),( p-value 0.36). There was no difference in change in CO, 2.10 (SD1.15) in the TT group vs 1.39 (SD 1.63) in TF group (p value 0.23). There was no difference in BORG RPE rating. In the term group, the mean change in HR from rest to 5 minutes was 15bpm (SD 8.40) in TT group and 13bpm (SD 7.86) in TF group,( p-value 0.416). The median change in CO from rest to 5 minutes was 1.50 (0.78 to 2.42 IQR) in TT group vs 1.60 (0.65 to 3.0 IQR) in TF group. Conclusion: Providing chest compressions is associated with an increase in both heart rate and cardiac output. We did not identify difference between objective and subjective measures of fatigue between either technique in a preterm or term model.